Pemanfaatan Limbah Bulu Ayam Dalam Mewujudkan Wirausaha Mandiri Di Desa Nyiur Tebel Lombok Timur - Rahman, Muhammad Rizki; Ghina Briliana Fatin Octariana; Davina Puspa Ningrum; Dira Agnita Putri Widodo; Dwi Yan Resilia; Lena Yuliastini; Nurkurnia Sari; Rizki Faturrahman; Raden Mohammad Akbar Rafi; Rossy Jamalul Hoir; Romdhini, Mamika Ujianita (Jurnal Pengabdian Magister Pendidikan IPA, 2025)
The purpose of this community service program is to find a new way to convert chicken feather waste into environmentally friendly and valuable animal feed. As an alternative to animal feed, chicken feather waste contains high protein. In this activity, the community is educated on how to process chicken feathers to support the sustainability of livestock farming and reduce environmental pollution. This program involves local farmers, small business groups, and academics. The results of the community service show that animal feed products made from chicken feather waste can increase feed efficiency, reduce production costs, and provide the community with new business opportunities. As a result, this project is expected to help improve community welfare in a sustainable manner and become a model for the application of appropriate technology in managing chicken feather waste.